Comparison of GeneXpert Results of Adult Pulmonary Tuberculosis (TB) Patients with Human Immunodeficiency Virus (HIV) without HIV Infection at three private hospitals in Jakarta - Fachri, Muhmmad; Pramesti, Salsabila Widya; Akaputra, Risky; Yanti, Fitri (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2024)
Background: Tuberculosis (TB) is a bacterial infection caused by Mycobacterium TB. According to the International Standard for TB Care (ISTC), Human Immunodeficiency Virus (HIV) is one of the main comorbidities in TB. Purposes: To compare the positivity rate of GeneXpert in diagnosing TB to suspected TB adult patients with and without HIV infection at three private hospitals in Jakarta. Methods: This study uses a cross-sectional approach; the data comes from medical records. The sampling technique in this research uses the cluster sampling formula. The inclusion criteria in this study were adult pulmonary TB patients more than 18 years of age, patients with pulmonary TB, and patients who had complete medical record data, and the exclusion criteria were patients who did not have GeneXpert examination results and adult pulmonary TB patients who did not have laboratory results of HIV Rapid test results. Statistical analysis using the Chi-Square statistical test. Results: A total of 24 adult pulmonary TB patients with HIV and positive GeneXpert were identified, whereas 13 adult TB patients with HIV and positive GeneXpert were identified, and pulmonary TB patients without HIV and positive GeneXpert numbered 59, while those with positive GeneXpert numbered 15. There is a tendency for fewer positive GeneXpert values in Adult Pulmonary TB patients with HIV compared to those without HIV Infection. Statistically not significant (p 0.05) Conclusion: Adult pulmonary TB patients without HIV tend to have higher positive GeneXpert test results than adult pulmonary TB patients with HIV, and there is no statistically significant relationship.